Community-based Tourism Governance towards Sustainable Development in the Northern Mountainous Region of Vietnam: A Case Study of Hoa Binh Province - Hoang Thi Thu Huong; Muthia Evirayani; Hanne Derau; Louna Dayekh; Tzu-Ting Amanda Chi; Chloé Ledune; Giang Van Trong; Nguyen Thi Hong Van; Nguyen Thi Hue; Pham Thi Nhan; Vu Huong Lan; Vu Kim Chi; et al. (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
Community-Based Tourism (CBT) stands as a pivotal approach for sustainable tourism and poverty alleviation in marginalized Northern Vietnamese rural communities. In Hoa Binh province, a region rich in ethnic diversity engaged in CBT, a research gap exists concerning CBT governance. This study addresses this gap by exploring how CBT governance is organized in five villages of Mai Chau and Da Bac district, Hoa Binh province, by identifying relevant actors, institutions, and resources, and how it addresses the challenge of sustainable (tourism) development. To this end, a combination of semi-structured interviews, focus groups, and observation were used. The results showed the complexity of CBT governance in Hoa Binh, and the many different manifestations of CBT in the different villages. The paper also analyzed factors that explain these differences, such as the historical or ethnic composition of the local community, biophysical conditions, community rules, and attributes of external factors. It also presents the complexity of the relationship between the development of CBT and sustainable development challenges. Received 7th February 2024; Revised 25th March 2024; Accepted 5th April 2024